Human papillomavirus detection in matched oral rinses, oropharyngeal and oral brushings of cancer-free high-risk individuals. (April 2019) - Donà, Maria Gabriella; Pichi, Barbara; Rollo, Francesca; Benevolo, Maria; Latini, Alessandra; Laquintana, Valentina; Pellini, Raul; Colafigli, Manuela; Frasca, Mirko; Giuliani, Massimo; Cristaudo, Antonio
Highlights: HPV detection rate is higher in oral rinses than site-specific brushings. HPV status agreement between rinses and brushings is poor, particularly for HPV-positive findings. More HPV types were found in the rinse, which were not isolated in the matched brushings. HPV infections revealed in oral rinses could not be traced back to the oropharynx or oral cavity. Abstract: Objectives: The detection of oral Human Papillomavirus (HPV) may be of clinical utility because of the major role HPV plays in the etiology of oropharyngeal cancer. However, oral HPV testing is not standardized and the best sampling method has yet to be identified. We aimed to compare HPV findings in matched oral rinse-and-gargles (rinses), oropharyngeal brushings and oral brushings. Materials and methods: HPV-DNA was investigated using Linear Array in samples collected from cancer-free individuals at increased risk for oral HPV. Results: 163 oral rinses already tested for HPV were selected. The matched oropharyngeal (n = 163) and oral brushings (n = 100) were analyzed. The detection rate for any HPV, high-risk (HR)-HPVs and HPV16 was significantly higher in rinses than brushings. The overall agreement for any HPV between rinses and oropharyngeal brushings was 51.2% (Cohen K: 0.14, 95% CI: 0.07–0.21). The proportion of positive agreement was 16.8%. The overall agreement for HR-HPVs was 74.1% (Cohen K: 0.20, 95% CI: 0.07–0.33). The genotype-specific profile of rinses and brushings which were concomitantly HPV-positive only partially overlapped in cases with multiple infections, with more genotypes detected in the rinse, which were not isolated in the corresponding brushings. Conclusion: The agreement for HPV status between rinses and brushings is poor, particularly for the HPV-positive findings. Despite the fact that the origin of the HPV-infected cells present in the oral rinse is unclear, since they could not be traced back to the oropharynx or oral cavity, oral rinses provided the highest detection rate for HR-HPVs and HPV16.